Promotion of rural employment for poverty reduction International Labour Conference, 97th Session 2008.. (Report (International Labour Conference), 2008)
This report adopts a decent work perspective to approach the challenge of promoting employment and reducing poverty in rural areas by examining issues of employment, social protection, rights and social dialogue in rural areas in an integrated way.